Pengaruh Work-Life Balance terhadap Komitmen Organisasi melalui Kepuasan Kerja - Alfianto, Rizeta Septiana; Hadi, Hafid Kholidi (Universitas Negeri Surabaya, 2024)
Organisational commitment is not just about ensuring that employees remain loyal to the company but is also a crucial factor in the company's success. Aspects that are influential on organisational commitment include work-life balance and job satisfaction. This research aims to analyse and prove the influence of work-life balance on organisational commitment through job satisfaction at Bank X. This quantitative research is analysed using Partial Least Square (PLS) data analysis techniques with the help of SmartPLS software version 3.2.9. The research sample was based on a total sampling technique, using 102 permanent employees of Bank X as respondents. Data were collected through questionnaires and measured using the Likert scale. The results of this study indicate that work-life balance has a significant positive effect on organisational commitment, work-life balance has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on organisational commitment, and job satisfaction can mediate the effect of work-life balance towards organisational commitment. The implications of this research require companies to implement work-life balance by providing opportunities for employees to have holidays. They also have to pay attention to employee job satisfaction because it can support the growth of organisational commitment in employees.